PENGARUH LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DEPARTEMEN P&GA (PERSONALIA AND GENERAL AFFAIR) PT JAPFA COMFEED INDONESIA, Tbk SIDOARJO - AGFAN PRAYOGATAMA, DOVI (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to analyze the influence of physical work environment on employee performance through job satisfaction as a variable as intervening variable in P & GA (Personnel & General Affair) department of PT Japfa Comfeed Indonesia, tbk unit of Sidoarjo. The approach used in this research is quantitative approach. The population is 104 employees, the sample technique used is using sample random sampling with slovin formula which amounted to 80 employees. Data analysis technique used is Structural Equation Model Partial Least Square with the help of SmartPLS 3.0 software. The results showed that the physical work environment does not affect the performance of employees with an average value of 1.197. While the physical work to work satisfaction ligkungan there is a direct and significant influence with the average value of 48.198. There is also direct and significant influence between job satisfaction variable to employee performance variable with average value 3,384. Keywords : Physical Work Environment, Job Satisfaction, Employee Performance